Multiple warehouse to customer site optimization study in support of a company strategic customer service initiative - Marckini, Scott (My University, 2019)
In the food ingredient supply chain, distributors play a vital role in moving and storing product from the supplier stage to the customer stage of the supply chain. In this process, high quality service can often be the differentiating factor among distribution companies. A large distribution company used the concept of superior customer service to successfully grow the company to the level of a nationwide food ingredient distributor. A strategic requirement of their service concept identified top tier customers who would receive “over the top service.” One example of that service would be guaranteed one-day delivery of ingredient orders. At the same time, the Operations Department was reviewing and closing warehouse locations across the country. In its growth, the company opened many warehouses, and some were identified as unnecessary. The question arose whether the new strategy might be hampered by the closure of too many warehouses or closing warehouses in the wrong locations. The objective of this thesis was to determine if that service guarantee was possible given the number and location of the company’s current warehouse assets relative to those priority customers. Utilizing data from the company’s transportation management system, top tier customer ship-to locations were listed and those currently exceeding the 1-day delivery were found. A model was selected that would identify those customers’ ship-to addresses that were within a 500-mile constraint of a target company warehouse. The figure of 500 miles was selected as this is the transportation industry recognized 1-day transit distance. This would be done for all target warehouse locations and the datasets merged and sorted. The results of the modeling demonstrated that all top tier customer ship-to locations were within one day’s delivery transit of a company warehouse. Those designated high value customers could have their ingredient orders delivered within one day of departure. By optimizing the company warehouses, identifying those within the one-day transit target, delivered freight costs were reduced significantly. Additionally, the results provided insight into redundancies that may allow for warehouse closures or realignments and cost savings to the company. These same redundancies also demonstrated potential competitive advantages in the sales and service of high value customers by providing superior distribution coverage potential minimizing risk to the customer’s ingredient supply chain. The results also suggested avenues for additional research to improve inventory efficiencies.
Keywords: Supply Chain; Logistics; Distribution; Customer Service; Optimization